2020
DOI: 10.23893/1307-2080.aps.05804
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and investigations of antimicrobial, antioxidant activities of novel di-[2-(3-alkyl/ aryl-4,5-dihydro-1h-1,2,4-triazol-5-one-4-yl)- azomethinephenyl] isophtalates and mannich base derivatives

Abstract: In this study, the synthesis of di-[2-(3-alkyl/aryl-4,5-dihydro-1H-1,2,4-triazol-5-one-4-yl)-azomethinephenyl] isophtalates (2a-g) from the reactions of 3-alkyl/ aryl-4-amino-4,5-dihydro-1H-1,2,4-triazol-5-ones (1a-g) with di-(2-formylphenyl) isophtalate is described. Then, the compounds 2 were treated with morpholine in the presence of formaldehyde to synthesize di-{2-[1-(morpholine-4-yl-methyl)-3alkyl(aryl)-4,5-dihydro-1H-1,2,4-triazol-5-one-4-yl]-azomethinephenyl} isophtalates (3a-g). The newly synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Heterocyclic molecules containing a five-membered 1,2,4-triazole skeleton and their derivatives have attracted particular attention due to the increase in the study area. Scientific studies have shown that molecules containing 1,2,4-triazole ring in their structure have different biological properties such as antibacterial, antimicrobial, analgesic, antifungal, anti-inflammatory, antihypertensive, antiviral, anticancer and antioxidant (Malbec et al, 1984;Holla et al, 2003;Shaker et al, 2005;Salgın Gökşen et al, 2007;Amir et al, 2008;Bagihalli et al, 2008;Kuş et al, 2008;Eswaran et al, 2009;Ahmad et al, 2017;Gundlewad & Patil, 2018;Yüksek et al, 2020;Acosta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic molecules containing a five-membered 1,2,4-triazole skeleton and their derivatives have attracted particular attention due to the increase in the study area. Scientific studies have shown that molecules containing 1,2,4-triazole ring in their structure have different biological properties such as antibacterial, antimicrobial, analgesic, antifungal, anti-inflammatory, antihypertensive, antiviral, anticancer and antioxidant (Malbec et al, 1984;Holla et al, 2003;Shaker et al, 2005;Salgın Gökşen et al, 2007;Amir et al, 2008;Bagihalli et al, 2008;Kuş et al, 2008;Eswaran et al, 2009;Ahmad et al, 2017;Gundlewad & Patil, 2018;Yüksek et al, 2020;Acosta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 1,2,4triazole derivatives exhibit a wide range of biological actions, including anticancer, antitumor, antibacterial, antioxidant, anti-inflammatory, and antipsychotic activities. [1][2][3][4][5][6][7][8][9] Furthermore, among many organic scaffolds, Schiff bases with an azomethine linkage are well-documented as promising and modifiable molecules in drug discovery. Several articles, about the synthesis of some Schiff bases with 4,5-dihydro-1H-1,2,4-triazol-5-one ring have also been published.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles, about the synthesis of some Schiff bases with 4,5-dihydro-1H-1,2,4-triazol-5-one ring have also been published. 4,[8][9][10][11][12][13] Among these, it is also known that 4,5-dihydro-1H-1,2,4-triazol-5-one ring has weak acidic properties, so that some 1,2,4-triazole and 4,5-dihydro-1H-1,2,4-triazol-5-one derivatives were titrated potentiometrically with TBAH in non-aqueous solvents. [11][12][13][14][15][16] Determining the pK a values of the active constituent of particular pharmaceutical preparations is crucial since the distribution, transport behavior, bonding to receptors, and contributions to the active constituent molecules' metabolic behavior depend on the ionization constant.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports, involving the synthesis of some N-arylidenamino-4,5-dihydro-1H-1,2,4-triazol-5-one derivatives (Schiff bases), have been published up to date [1][2][3][4][5][6][7][8][9]. 1,2,4-Triazole and 4,5-dihydro-1H-1,2,4triazol-5-one derivatives are investigated to show a broad spectrum of biological activities such as antimicrobial, antifungal, antihypertensive, hypoglycemic, analgesic, antiparasitic, antiviral, antiinflammatory, hypocholesteremic, antitumor, antioxidant, and anti-HIV properties [3,[5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%